1986
DOI: 10.1016/s0022-5347(17)45712-0
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Significance of Post-Irradiation Biopsy Results in Patients with Prostatic Cancer

Abstract: To evaluate the prognostic significance of post-irradiation biopsy results in patients with prostatic cancer, we reviewed the records of 803 patients who had been treated with pelvic lymph node dissection, radioactive gold seed implantation and external beam irradiation. Of the patients 124 had 1 or more biopsies within 6 to 36 months after completion of radiotherapy when there was no evidence of local or distant recurrence of tumor. Patients were followed for a mean of 64 months (range 14 to 175 months) and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(21 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…Scardino has shown a local tumor recurrence of 45% 'hen post-treatment (Gold 198 + external radiotherapy) iopsies were positive, compared to 11 % when biopsies ere negative [24]. Unfortunately the relationship beveen biopsy findings and the incidence of distant metasjses in his pNO group was not further evaluated.…”
Section: ]mentioning
confidence: 98%
“…Scardino has shown a local tumor recurrence of 45% 'hen post-treatment (Gold 198 + external radiotherapy) iopsies were positive, compared to 11 % when biopsies ere negative [24]. Unfortunately the relationship beveen biopsy findings and the incidence of distant metasjses in his pNO group was not further evaluated.…”
Section: ]mentioning
confidence: 98%
“…Scardino et al [20], as well as others, documented the adverse prognostic outcome associated with postradiation positive biopsies. Lee et al [21] demonstrated that pros tatic ultrasonography can be used to guide biopsies in patients who have previously undergone interstitial brachytherapy for management of localized prostate cancer.…”
Section: Management Of Postradiation Local Recurrencesmentioning
confidence: 95%
“…About 20% of patients with positive postradiation prostate biopsies have no evidence of disease at 10 y follow-up. 7,31 Undoubtedly, some positive biopsies may detect clinically latent cancers. Equally important is the almost 30% incidence of local and distant recurrences occurring in those with negative postradiation biopsies.…”
Section: ±7mentioning
confidence: 99%